2022
DOI: 10.3390/app12031053
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Photogrammetry Assessment in Comparison with a Compact Camera for Construction Management Applications

Abstract: Close-range photogrammetry (CRP) has proven to be a remarkable and affordable technique for data modeling and measurements extraction in construction management applications. Nevertheless, it is important to aim for making CRP more accessible by using smartphones on-site directly without a pre-calibration procedure. This study evaluated the potential of smartphones as data acquisition tools in comparison with compact cameras based on the quality and accuracy of their photogrammetric results in extracting geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The model was then developed using the SfM-MVS method with fixed pre-calibration (IO parameters were determined from the chessboard test and then considered constant). After confirming the IO stability of the Nikon D5200 camera and considering the low noise of Nikon cameras [ 74 ], the 3D model was treated as a reference. The models were compared in CloudCompare [ 105 ] using the cloud-to-cloud distance function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was then developed using the SfM-MVS method with fixed pre-calibration (IO parameters were determined from the chessboard test and then considered constant). After confirming the IO stability of the Nikon D5200 camera and considering the low noise of Nikon cameras [ 74 ], the 3D model was treated as a reference. The models were compared in CloudCompare [ 105 ] using the cloud-to-cloud distance function.…”
Section: Methodsmentioning
confidence: 99%
“…The most common solution is on-the-job calibration. Among the many smartphone photogrammetry publications, only a small part of them contain information on calibration [ 30 , 40 , 41 , 59 , 64 , 67 , 72 , 74 , 76 , 78 , 90 , 93 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review paper focusing on stereophotogrammetry and smartphone technology by Quinzi et al, 2022, concluded that “Stationary stereophotogrammetry devices showed a mean accuracy that ranged from 0.087 to 0.860 mm, portable stereophotogrammetry scanners from 0.150 to 0.849 mm, and smartphones from 0.460 to 1.400 mm.” [ 46 ]. The volumetric estimation errors are typically bigger in smartphone scanning than in photogrammetry [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As explained above, the JPEG Snack file contains embedded multimedia data, so the inputs to the JPEG Snack encoder can be portable network graphics (PNG) or JPEG-1 images taken from the camera, videos recorded with the camera, or audio recorded with a microphone. The sensors used for the images and videos are compact cameras [ 32 ], 360° cameras [ 33 ], digital single-lens reflex (DSLR), and adventure cameras. For audio, microphone sensors are used.…”
Section: Jpeg Snack Encoded Filementioning
confidence: 99%